Alkaloid variation in New Zealand kōwhai, Sophora species. (October 2015) - McDougal, Owen M.; Heenan, Peter B.; Jaksons, Peter; Sansom, Catherine E.; Smallfield, Bruce M.; Perry, Nigel B.; van Klink, John W.
Graphical abstract: A phytochemical investigation of eight New Zealand Sophora species has resulted in the identification of alkaloids of the sparteine, matrine, and cytisine quinolizidine types. Distribution was variable, but the seeds contained the highest concentrations of alkaloids. Highlights: Alkaloids were extracted and analysed from leaf and seed of 8 species of Sophora native to New Zealand. GC analyses showed cytisine, N -methyl cytisine, and matrine were generally the most abundant alkaloids. Quantitative analysis of two S. microphylla trees showed that the seeds were the richest source of alkaloids. S. microphylla leaf/twig had less alkaloids than seed, with only lower amounts in the bark and roots. There was no clear taxonomic grouping based on alkaloid composition. Abstract: Alkaloid contents of leaf and seed samples of eight species of Sophora native to New Zealand, plus Sophora cassioides from Chile are reported. Fifty-six leaf and forty-two seed samples were analysed for alkaloid content by proton nuclear magnetic resonance spectroscopy, which showed major alkaloids as cytisine, N -methyl cytisine and matrine. GC analyses quantified these and identified further alkaloid components. The alkaloids identified were cytisine, sparteine, and matrine-types common to Sophora from other regions of the world. Cytisine, N -methyl cytisine, and matrine were generally the most abundant alkaloids across all species with seeds containing the highest concentrations of alkaloids. However, there was no clear taxonomic grouping based on alkaloid composition. A quantitative analysis of various parts of two Sophora microphylla trees showed that the seeds were the richest source of alkaloids (total 0.4–0.5% DM), followed by leaf and twig (0.1–0.3%) and then bark (0.04–0.06%), with only low amounts (<0.02%) found in the roots. This study represents the most comprehensive phytochemical investigation of New Zealand Sophora species to date and presents data for three species of Sophora for which no prior chemistry has been reported.